Necessary for some, and helpful for all: preparing music educators to reach every student (Orfeu, 2023)
This paper puts forth the argument that the field of pre-service music teacher education in the United States must include coursework in accessible music education in order to prepare music educators to teach today’s students effectively. The percentage of students with disabilities and diagnoses in today’s schools is rising, and music educators in the U.S. are not adequately prepared to teach these students. Using the framework of “necessary for some, and helpful for all,” the paper asserts that incorporating some of the strategies and approaches of accessible music education – specifically, Universal Design for Learning and Differentiated Instruction – into undergraduate music teacher education programs would greatly increase the effectiveness of U.S. music teacher preparation.
Keywords: accessible music education; pre-service music education; universal design for learning; differentiated instruction